Religions of the world - Hopfe, Lewis M. 1935-1992 (Prentice Hall, 2001)
Offers accurate, comparative descriptions of a broad range of religions and explores living religions in terms of historical and cultural factors that produced them, the lives of their founders, their basic teachings, and their historical development and current status in the world.